Screening for psychosocial distress among patients with cancer: implications for clinical practice, healthcare policy, and dissemination to enhance cancer survivorship - Ehlers, Shawna L; Davis, Kimberly; Bluethmann, Shirley M; Quintiliani, Lisa M; Kendall, Jeffrey; Ratwani, Raj M; Diefenbach, Michael A; Graves, Kristi D (Translational behavioral medicine, 2019)
Accreditation standards are at the forefront of evolving healthcare systems, setting metrics for high-quality care. Healthcare outcomes (health, experience, cost, provider satisfaction/burn out) are becoming mutual goals of the patient, provider, payer, and healthcare system. Achieving high-quality outcomes in cancer care necessitates collaboration among interdisciplinary teams of clinical providers, administrators, patient advocates, caregivers, and researchers. Dissemination and implementation science provides necessary frameworks to organize the efforts of these implementation teams, inclusive of identifying facilitators and barriers to implementation of accreditation standards. Since 2015, cancer distress screening has been mandated for continued cancer center accreditation by the American College of Surgeon's Commission on Cancer. Cancer centers have thus become real world implementation laboratories. We present the current context of distress screening, highlighting prior research and key areas of future research. We consider multiple levels of cancer care delivery and the use of interdisciplinary teams to help cancer center teams adopt, implement, and maintain efficient distress screening programs. Finally, we present a case study to identify methods for successful implementation of distress screening at one cancer center and then describe efficiencies that can be introduced using elements from human factors engineering, e- and m-health screening platforms, and community partnerships.